Meningitis: latest developments. - Wong,HEE; Hey,A; Tang,CM; Kroll,JS; Langford,PR (Future Microbiol, 2011)
The aim of the meeting was to consider the latest advances in meningitis, covering epidemiology, pathogenic mechanisms, host-interactive biology and vaccines in a variety of bacteria, fungi and protozoa that cause meningitis. The program was comprised of speakers from the UK, as well as international presenters, who had been invited and offered selected papers. Owing to space limitations, only the four bacteria with multiple invited speakers will be considered here.